2018
DOI: 10.1029/2018ja025819
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Kinetic Energy Budget of the Polar Wind Outflow

Abstract: Ionospheric outflow from the polar cap through the polar wind plays an important role in the evolution of the atmosphere and magnetospheric dynamics. Both solar illumination and solar wind energy input are known to be energy sources of the polar wind. However, observational studies of the energy transfer from these two energy sources to the polar wind are difficult. Because of their low energy, polar wind ions are invisible to regular ion detectors onboard a positively charged spacecraft. Using a new technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Li et al (2017) have found approximately 237,000 records of cold ion density, velocity, and particle flux ( F P = nV || ) at 1,000 km altitude. Their tracing results have been used in the study by Li et al (2018) and in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al (2017) have found approximately 237,000 records of cold ion density, velocity, and particle flux ( F P = nV || ) at 1,000 km altitude. Their tracing results have been used in the study by Li et al (2018) and in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The dipole tilt angle modulates the solar zenith angle (SZA) and hence the solar irradiation over the polar cap around the dipole axis. This effect has been addressed in both simulations (e.g., Barakat et al, 2015;Glocer et al, 2012;Su et al, 1998) and observations (e.g., Kitamura et al, 2011;Li et al, 2017Li et al, , 2018Maes et al, 2017). Furthermore, the dipole tilt angle also influences magnetosphere-ionosphere coupling as simulated by Cnossen and Richmond (2012).…”
Section: Introductionmentioning
confidence: 99%
“…Those lowenergy ions can gain energy through solar illumination which changes the ionospheric scale height (Maes et al 2015). However, according to Li et al (2018) the energy transfer efficiency of the solar wind is 6-7 orders of magnitude higher than the energy originating from the solar illumination. Solar illumination of the polar cap is much affected by the tilt of the geomagnetic dipole.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have employed the above technique of combining EFW and EDI measurements to study the outflow of cold ions (André et al, 2015;Engwall et al, 2008Engwall et al, , 2009Haaland et al, 2012Haaland et al, , 2015Li et al, 2012Li et al, , 2013Li et al, , 2017Li et al, , 2018Maes et al, 2017).…”
Section: Wake Effects and Ion Outflowmentioning
confidence: 99%